Glecaprevir/Pibrentasvir in patients with chronic HCV genotype 3 infection: An integrated phase 2/3 analysis. Issue 3 (11th December 2018) - Flamm, Steven; Mutimer, David; Asatryan, Armen; Wang, Stanley; Rockstroh, Jürgen; Horsmans, Yves; Kwo, Paul Y.; Weiland, Ola; Villa, Erica; Heo, Jeong; Gane, Edward; Ryder, Stephen D.; et al.
Summary: Glecaprevir coformulated with pibrentasvir (G/P) is approved to treat hepatitis C virus (HCV) infection and was highly efficacious in phase 2 and 3 studies. Treating HCV genotype (GT) 3 infection remains a priority, as these patients are harder to cure and at a greater risk for liver steatosis, fibrosis progression and hepatocellular carcinoma. Data were pooled from five phase 2 or 3 trials that evaluated 8‐, 12‐ and 16‐week G/P in patients with chronic HCV GT3 infection. Patients without cirrhosis or with compensated cirrhosis were either treatment‐naïve or experienced with interferon‐ or sofosbuvir‐based regimens. Safety and sustained virologic response 12 weeks post‐treatment (SVR12) were assessed. The analysis included 693 patients with GT3 infection. SVR12 was achieved by 95% of treatment‐naïve patients without cirrhosis receiving 8‐week (198/208) and 12‐week (280/294) G/P. Treatment‐naïve patients with cirrhosis had a 97% (67/69) SVR12 rate with 12‐week G/P. Treatment‐experienced, noncirrhotic patients had SVR12 rates of 90% (44/49) and 95% (21/22) with 12‐ and 16‐week G/P, respectively; 94% (48/51) of treatment‐experienced patients with cirrhosis treated for 16 weeks achieved SVR12. No serious adverse events (AEs) were attributed to G/P; AEs leading to study drug discontinuation were rare (<1%). G/P was well‐tolerated and efficacious for patients with chronic HCV GT3 infection, regardless of cirrhosis status or prior treatment experience. Eight‐ and 12‐week durations were efficacious for treatment‐naïve patients without cirrhosis and with compensated cirrhosis, respectively; 16‐week G/P was efficacious in patients with prior treatment experience irrespective of cirrhosis status.